The influence of family environment on the choice of business strategy: Innovation culture as a mediating variable - Setiawan, Antonius Singgih; Panjaitan, Delfi (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
This study aims to see whether the family environment can have a positive impact on the development of a company's innovation culture and influence the orientation of the company's business strategy choices. However, this study also aims to see whether the culture of innovation can impact the orientation of business strategy choices. Finally, this study also aims to prove the culture of innovation as a variable that mediates the relationship between the family environment and business strategy choices. Using a sample of 178 respondents (response rate 89%) with entrepreneur respondents in the city of Palembang, the research hypothesis was tested using Structural Equation Modeling (SEM) Partial Least Squares (PLS) analysis with Warp PLS software version 5.0. The results concluded that the family environment has a positive effect on the culture of innovation and business strategy choices; on the other hand, the culture of innovation has an effect on business strategy choices, and finally, the culture of innovation mediates the relationship between the family environment and business strategy choices in firms in Palembang.